2015
DOI: 10.1200/jco.2015.33.3_suppl.591
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic clinical factors in pretreated colorectal cancer patients receiving regorafenib: Implications for clinical management.

Abstract: Background:We assessed the impact on survival of angiogenesis and inflammation-related factors, particularly LDH serum levels, platelet, neutrophil and lymphocyte counts, and neutrophil-to-lymphocyte ratio (NLR), in metastatic colorectal cancer patients receiving regorafenib monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…An elevated NLR is considered to be associated with elevated circulating concentrations of these cytokines, which offers an insight into mechanisms underlying an elevated NLR (30,31). Nevertheless, the cutoff points of NLR proposed in previous studies differ, including NLR thresholds of 2.3, 4.02 or 5 in gastric cancer (14,32,33), 0.38, 2.4 or 3 in colorectal cancer (15,34,35), 2.3 or 2.5 in NSCLC (10,36), and consensus has not been established. The heterogeneity of those studies may contribute to the different results.…”
Section: Discussionmentioning
confidence: 93%
“…An elevated NLR is considered to be associated with elevated circulating concentrations of these cytokines, which offers an insight into mechanisms underlying an elevated NLR (30,31). Nevertheless, the cutoff points of NLR proposed in previous studies differ, including NLR thresholds of 2.3, 4.02 or 5 in gastric cancer (14,32,33), 0.38, 2.4 or 3 in colorectal cancer (15,34,35), 2.3 or 2.5 in NSCLC (10,36), and consensus has not been established. The heterogeneity of those studies may contribute to the different results.…”
Section: Discussionmentioning
confidence: 93%
“…A previously well-conducted study comprising 208 regorafenib-treated patients demonstrated an association between high neutrophil, high platelet, low lymphocyte count and/or high neutrophil–lymphocyte ratio with prognosis. 26 Due to the stringent inclusion criteria of our study, our data distribution did not allow to use the same cut-off used in the study by Del Prete and colleagues and median values were used instead. Notwithstanding small numbers and patient selection based on trial inclusion/exclusion criteria, no significant correlation with efficacy was found with any of the above-mentioned factors (see online appendix tables A8 and A9).…”
Section: Resultsmentioning
confidence: 99%
“…Lymphocytes usually function as pivotal tumour suppressors by inducing cytotoxic cell death and producing cytokines that inhibit cancer cell proliferation and metastatic activity [34,35]. Elevated NLR, caused by lymphocytopenia and/or a high neutrophil count, may lead to a poor immune response to malignancy and an increased potential for tumour recurrence [33,[36][37][38][39][40]. Thus, NLR is recognized as an efficient inflammationbased prognostic parameter in solid tumours [29].…”
Section: Discussionmentioning
confidence: 99%